2019
DOI: 10.1007/s00426-019-01197-z
|View full text |Cite
|
Sign up to set email alerts
|

Subjective emotional arousal: an explorative study on the role of gender, age, intensity, emotion regulation difficulties, depression and anxiety symptoms, and meta-emotion

Abstract: Subjective emotional arousal in typically developing adults was investigated in an explorative study. 177 participants (20–70 years) rated facial expressions and words for self-experienced arousal and perceived intensity, and completed the Difficulties in Emotion Regulation scale and the Hospital Anxiety and Depression scale (HADS-D). Exclusion criteria were psychiatric or neurological diseases, or clinically relevant scores in the HADS-D. Arousal regarding faces and words was significantly predicted by emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 86 publications
0
28
0
1
Order By: Relevance
“…Although girls appear to be suffering more than boys in response to COVID-19, our results show that boys are also impacted and thus should not be overlooked in prevention and intervention efforts. Prior research suggests boys' delayed response may be related to higher levels of emotional regulation, lower levels of socioemotional awareness and/or societal norms and pressures for males to suppress negative emotions more so than girls (Deckert et al, 2020;Hagler et al, 2016;Pollastri et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although girls appear to be suffering more than boys in response to COVID-19, our results show that boys are also impacted and thus should not be overlooked in prevention and intervention efforts. Prior research suggests boys' delayed response may be related to higher levels of emotional regulation, lower levels of socioemotional awareness and/or societal norms and pressures for males to suppress negative emotions more so than girls (Deckert et al, 2020;Hagler et al, 2016;Pollastri et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Casual inferences from effective connectivity findings also indicated that amygdala hyperarousal is neither adequately transmitted to, nor sufficiently inhibited by cognitive control hubs (see (Stuhrmann, Suslow, & Dannlowski, 2011) for attenuated bottom‐up/top‐down amygdala‐prefrontal connections in MDD). In addition, behavioral evidences implied that higher values in stimulus‐specific subjective arousal eventuates to inefficient and costly implementation of cognitive control strategies (Sheppes et al, 2014), specifically in people with greater depression scores (Deckert, Schmoeger, Auff, & Willinger, 2019). Altogether, it seems that overburden of emotional reactivity in amygdala may inversely affect cognitive control processes in prefrontal cortices, which leads to diminished regulatory actions.…”
Section: Discussionmentioning
confidence: 99%
“…Casual inferences from effective connectivity findings also indicated that amygdala hyperarousal is neither adequately transmitted to, nor sufficiently inhibited by cognitive control hubs (see (Stuhrmann, Suslow, & Dannlowski, 2011) for attenuated bottom-up/top-down amygdala-prefrontal connections in MDD). In addition, behavioral evidences implied that higher values in stimulus-specific subjective arousal eventuates to inefficient and costly implementation of cognitive control strategies (Sheppes et al, 2014), specifically in people with greater depression scores (Deckert, Schmoeger, Auff, & Willinger, 2019). Altogether, it seems that overburden of emotional reactivity in amygdala may inversely affect cognitive control processes in prefrontal cortices, which leads to diminished regulatory actions.…”
Section: Discussionmentioning
confidence: 99%